How People Recall Search Result Lists - Teevan, Jaime (Proceedings of the ACM Conference on Human Factors in Computing Systems (CHI 2006), Montreal, Canada, 2006)
People commonly interact with lists of information - incoming emails are listed in a person's Inbox, search engines return lists of results, news stories appear as lists on newspaper Web sites, and people navigate file systems by listing directory contents. While the changes that occur to a list can be interesting - a new search result is interesting to the person searching for new information - changes are often secondary to the primary goal of using information. New search results are inconsequential when a person wants to summarize a set of results or return to a previously viewed Web page. This paper presents a study of which aspects of a list are memorable and thus are likely to be noticed when they change, and which are not memorable and thus are unlikely to be missed if changed. The study shows that what people remember about a list item is a function of their interaction with the item and the item's location in the list.